2003
DOI: 10.1074/jbc.m211787200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phosphoinositide 3-Kinases Mediate Mast Cell Degranulation in Response to G-protein-coupled VersusFcεRI Receptors

Abstract: Chem. 276, 17213-17220). We now examine the role of Class IA PI 3-kinases isoforms in degranulation itself, using a single-cell degranulation assay that measures the binding of fluorescently tagged annexin V to phosphatidylserine in the outer leaflet of the plasma membrane of degranulated mast cells. Consistent with previous data, antibodies against p110␦ and p110␤ blocked Fc⑀R1-mediated degranulation in response to Fc⑀RI ligation. However, antigen-stimulated degranulation was also inhibited by antibodies agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…This could explain the presence of a calciumdependent early Rac and Cdc42 activation phase, even in the presence of the PLCc inhibitor. Work from our laboratory and others showed a requirement for PI3K in mast cell degranulation and calcium influx [8,10,12], and PLCc-independent phosphatidylinositol 3,4,5-triphosphate-sensitive calcium channels at the plasma membrane have been characterized [9]. However, PI3K is not required for activation of Rac and Cdc42 in mast cells [10,13,24], where it may in fact be downstream of Rac [24,52].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could explain the presence of a calciumdependent early Rac and Cdc42 activation phase, even in the presence of the PLCc inhibitor. Work from our laboratory and others showed a requirement for PI3K in mast cell degranulation and calcium influx [8,10,12], and PLCc-independent phosphatidylinositol 3,4,5-triphosphate-sensitive calcium channels at the plasma membrane have been characterized [9]. However, PI3K is not required for activation of Rac and Cdc42 in mast cells [10,13,24], where it may in fact be downstream of Rac [24,52].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that PI3K is essential for degranulation in antigen-responsive mast cells [11,12]. However, it has been reported that Rac activation in response to antigen stimulation in mast cells is PI3K-independent [24].…”
Section: Plcc Inhibition Increases the Activation Of Rac And Cdc42mentioning
confidence: 99%
See 2 more Smart Citations
“…Vesicular fusion to plasma membrane was visualized with FITC-annexin V, as described previously (32). Briefly, RBL-FPR cells were grown on a glass coverslip for 48 h, washed once with HBSS, and incubated with 10 M cytochalasin B and a 1/20 dilution of FITC-annexin V in HBSS-HB for 15 min on ice and then 15 min at 37°C.…”
Section: Annexin V Bindingmentioning
confidence: 99%